Microscopic studies on the transition between the sigmoid sinus, the superior bulb of the jugular vein and the first portion of the internal jugular vein - Piffer, C. R. (Karger Publishers, 1979)
The author studied the structure of the tissue components of the tunicae of the terminal segment of the sigmoid sinus, particularly at the level of the transition between the sigmoid sinus, the superior bulb of the jugular vein and the first portion of the human internal jugular vein; it was established that the transition between the sigmoid sinus and the first portion of the internal jugular vein occupies the whole extension of the superior bulb of the jugular vein up to the inferior third of the first portion of this vessel. These vascular walls exhibit a structure similar to that of the dura, i.e. the tunica adventitia is formed by fascicles of collagenic fibers which describe discontinuous spirals, more open proximal to the beginning of the first portion of the internal jugular vein. Approximately in the inferior third of the first portion of the internal jugular vein, there appear fascicles of smooth muscle fibers which are arranged similarly to those of the venous walls. The tunica intima of these vascular segments exhibits an endothelium resting on a network of elastic fibers which may play the role of an internal elastic lamina. From the bony border of the jugular foramen there originates a connective system whose fascicles of collagenic and elastic fibers incorporate to the wall of the internal jugular vein after describing a stretch in spiral around the vascular lumen.
Keywords: histology; human cell; internal jugular vein; jugular foramen; normal human; peripheral vascular system; venous circulation; Collagen; Cranial Sinuses; Dura Mater; Elastic Tissue; Human; Jugular Veins; Microscopy; Muscle, Smooth, Vascular